Principles of purpose - Munroe, Myles (U.S.A: Universal, 2013)
Myles Munroe explains how you can make your dreams and hopes a living reality.Your success is not dependent on the state of the economy or what the job market is like. You do not need to be hindered by the limited perceptions of others or by a lack of resources. Discover time-tested principles that will enable you to fulfill your purpose no matter who you are or where you come from. You were not meant for mundane or mediocre life. You do not exist just to earn a payback .Revive your passion for living.Pursue your dream. Discover your purpose and find your true life.